Induction of osteogenic differentiation of bone marrow stromal cells on 3D polyester-based scaffolds solely by subphysiological fluidic stimulation in a laminar flow bioreactor - Yamada, Shuntaro (J Tissue Eng, 2021)
The fatal determination of bone marrow mesenchymal stem/stromal cells (BMSC) is closely associated with mechano-environmental factors in addition to biochemical clues. The aim of this study was to induce osteogenesis in the absence of chemical stimuli using a custom-designed laminar flow bioreactor. BMSC were seeded onto synthetic microporous scaffolds and subjected to the subphysiological level of fluid flow for up to 21 days. During the perfusion, cell proliferation was significantly inhibited. There were also morphological changes, with F-actin polymerisation and upregulation of ROCK1. Notably, in BMSC subjected to flow, mRNA expression of osteogenic markers was significantly upregulated and RUNX2 was localised in the nuclei. Further, under perfusion, there was greater deposition of collagen type 1 and calcium onto the scaffolds. The results confirm that an appropriate level of fluid stimuli preconditions BMSC towards the osteoblastic lineage on 3D scaffolds in the absence of chemical stimulation, which highlights the utility of flow bioreactors in bone tissue engineering.